Does Surgeon Subjective Nerve Sparing Score Predict Recovery Time of Erectile Function Following Robot-Assisted Radical Prostatectomy?. (1st June 2015) - Kang, Sung Gu; Schatloff, Oscar; Haidar, Abdul Muhsin; Samavedi, Srinivas; Palmer, Kenneth J.; Cheon, Jun; Patel, Vipul R.
Abstract: Introduction: During robot-assisted radical prostatectomy (RARP), the quality of nerve sparing (NS) was usually classified by laterality of NS (none, unilateral, and bilateral) or degree of NS (none, partial, and full). Recently, side-specific NS have been more frequently performed, but previous NS grading system might not reflect the differential NS in each side. Aim: Herein, we assessed whether a subjective NS score (NSS) incorporating both degree of NS and NS laterality can predict the time to potency recovery following RARP. Methods: Data were analyzed from 1, 898 patients who had left and right neurovascular bundle sparing quality scores and at least one year of follow-up after RARP was performed between January 2008 and October 2011. Main Outcome Measures: Cox proportional hazard method analyses were used to determine predictive factors for early recovery. Multivariate linear regression models were used to assess subjective NSS in an effort to predict time to potency recovery. Subjective NSSs were compared to a model based on the three grades according to laterality and degree. Results: Time to potency recovery showed a statistically significant difference in favor of higher NSS by the Cox proportional hazard regression analysis (NSS 0 vs. NSS 5–6, 7–8, and 9–10; P  < 0.01). The regression model indicated that the statistical significance of the subjective NSS covering the differential NS is not different from that of the conventional three-grade scales, while it has a higher R 2 . The regression equation with subjective NSS was as follows: Log (Time) = 5.163 − (0.035 × SHIM Score) + 0.028 Age − (0.101 × Subjective  NSS) . Conclusion: The subjective NSS can reflect NS degree for each side based on the visual cues. Regression model can be used to help inform the patient about the time to postoperative potency regain, which is an important patient concern following RARP.